The end of history and the last king Achaemenid ideology and community identity in Ezra-Nehemiah - Janzen, David 1968- (London Bloomsbury Publishing Plc, 2021)
Cover -- Title -- Copyright -- Contents -- List of Abbreviations -- Chapter 1 Introduction: Community Identity, Achaemenid Ideology, and the Composition of Ezra-Nehemiah -- 1. The Approach and Outline of the Argument -- 2. The Composition and Authorship of Ezra-Nehemiah -- 3. The Persian-Period Date of Ezra-Nehemiah -- Chapter 2 Community Identity in Ezra-Nehemiah -- 1. Ezra 1-6: The Ideal Generation -- 2. Ezra 7-10: The Epigone, Part 1 -- 3. Nehemiah 1:1-13:3: The Epigone, Part 2 -- 4. Nehemiah 13:4-34: The Epigone, Conclusion -- Chapter 3 The Beneficent King in Achaemenid Ideology and in Ezra-Nehemiah -- 1. Introduction: The Background of Achaemenid Ideology -- 2. Achaemenid Ideology, Part 1: The Beneficent King -- 3. Community and Beneficent King in Ezra-Nehemiah -- 4. Conclusion: From Colonizers to Colonized -- Chapter 4 The King, God, and Torture -- 1. Achaemenid Ideology, Part 2: The Necessity of Torture -- 2. The Community and Imperial and Divine Violence in Ezra-Nehemiah -- 3. The End of History and the Last King, Part 1 -- Chapter 5 Empire and Ideology in Persian-Period Judah -- 1. Ezra-Nehemiah within the Temple Community's Factions -- 2. Empire and Community Identity in the Persian-Period Temple Community -- 3. Post-exilic Prophetic Critiques of Empire -- 4. Conclusion: The End of History and the Last King, Part 2 -- Chapter 6 Conclusion: The Struggle over Community Identity in the Persian Period -- Bibliography -- Index of References -- Index of Authors.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Ezra-Commentaries; Bible.-Nehemiah-Commentaries; Achaemenid dynasty-559-330 B.C; Electronic books